Gg → h → τ+τ- at the upgraded Fermilab Tevatron - Belyaev, Alexander; Han, Tao; Rosenfeld, Rogério [UNESP] (Springer Nature, 2003)
We study the neutral Higgs boson production via the gluon fusion process with the τ+τ- final state at the upgraded Fermilab Tevatron, including a complete simulation of signal channels and leading background processes. For the SM Higgs boson, this h → τ +τ- channel may provide important addition for the Higgs boson discovery in the mass range 120 -140 GeV. In minimal supersymmetric models, natural enhancement for the signal rate over the SM expectation makes the h, H, A → τ+τ- signal observable for large tan β and low MA, which may lead to full coverage for SUSY Higgs parameters at the Tevatron with a moderate integrated luminosity. © SISSA/ISAS 2003.
Keywords: Hadronic Colliders; Higgs Physics; Standard Model; Supersymmetric Standard Model